High CO2‐Capture Ability of a Porous Organic Polymer Bifunctionalized with Carboxy and Triazole Groups. Issue 35 (23rd July 2013) - Xie, Lin‐Hua; Suh, Myunghyun Paik
Abstract A new porous organic polymer, SNU‐C1, incorporating two different CO2‐attracting groups, namely, carboxy and triazole groups, has been synthesized. By activating SNU‐C1 with two different methods, vacuum drying and supercritical‐CO2 treatment, the guest‐free phases, SNU‐C1‐va and SNU‐C1‐sca, respectively, were obtained. Brunauer–Emmett–Teller (BET) surface areas of SNU‐C1‐va and SNU‐C1‐sca are 595 and 830 m2g−1, respectively, as estimated by the N2‐adsorption isotherms at 77 K. At 298 K and 1 atm, SNU‐C1‐va and SNU‐C1‐sca show high CO2 uptakes, 2.31 mmol g−1 and 3.14 mmol g−1, respectively, the high level being due to the presence of abundant polar groups (carboxy and triazole) exposed on the pore surfaces. Five separation parameters for flue gas and landfill gas in vacuum‐swing adsorption were calculated from single‐component gas‐sorption isotherms by using the ideal adsorbed solution theory (IAST). The data reveal excellent CO2‐separation abilities of SNU‐C1‐va and SNU‐C1‐sca, namely high CO2‐uptake capacity, high selectivity, and high regenerability. The gas‐cycling experiments for the materials and the water‐treated samples, experiments that involved treating the samples with a CO2‐N2 gas mixture (15:85, v/v) followed by a pure N2 purge, further verified the high regenerability and water stability. The results suggest that these materials have great potential applications in CO2 separation.